Assessment Of The Impact Of Catchments Providing Water To Marj Sanour & Design Of Water Collection System(Hydrologic Analysis) - Isam Khasib; Farouq Hamad; Bashar Ibrahim (My University, 2018)
Marj Sanour is one of the major agricultural areas in Palestine. It is being utilized extensively in providing agricultural crops and profits for the farmers. In the recent years it is noticeable that due to the rainfall, Sanour valley becomes a pond that submerges all the fields and crops, so the crops & the water inside the valley are totally lost. This project describes the different reasons for this serious problem, the impact of the catchments providing water to the valley and the provided solutions. A Model (GIS and HEC) will be developed to show the catchments and the main streams that provide water to the valley. Moreover, a water collection system will be designed using Storm Cad to be used in collecting water from the valley. To facilitate data processing & assessment, GIS software will be utilized. It is expected a huge effect on the land & crops planted therein and a water collection system has to be designed to collect water and direct it toward an underground well exists in the valley in a process called artificial recharge. A cost analysis is a perfect way in evaluating the possibility of implementing the water collection system. Finally; as a graduation project, our project had not been done before.